Analysis of Beginning Reading Ability in Elementary School: Analisis Kemampuan Membaca Permulaan di Sekolah Dasar - Heffy Setya Eka Sari; Vevy Liansari (Academia Open, 2022)
This research was motivated by the fact that in the first grade of SDN Keret Krembung there were students who experienced the ability to read early. Therefore, the researcher wants to analyze the abilities experienced by students in beginning reading. The purpose of this research is to find out what is being faced by class I students so that they experience early reading skills. This study uses a qualitative research approach, this research has a special approach in the field, this study uses 2 student subjects. Data was collected using observation, interviews, and documentation. Test the validity of the data is done by triangulation techniques or methods. The results showed that the abilities experienced by first-class students in reading the beginning of SDN Keret Krembung were: (1) they could pronounce the letters of the alphabet, (2) they could identify letters, (3) they could recognize vowels, (4) they could distinguish between letters and letters. letter.